Penggunaan Aplikasi Canva Pada Model Project-based Learning (PjBL) Untuk Meningkatkan Hasil Belajar Siswa SMA Negeri 11 Banda Aceh - Suraiya, Nana; Mustofa, Achmad; Razak, A.; Zara, Wilda; Sofiya, Aya (Buletin Literasi Budaya Sekolah, 2024)
This research was conducted with the aim of improving student learning outcomes in class X IPAS 8 by applying the Project Base Learning (PJBL) learning model. This research was conducted at SMA Negeri 11 Banda Aceh in the even semester of the 2022/2023 school year involving 30 female students. Data collection techniques used are observation, performance of learning outcomes and documentation. Data analysis used descriptive analysis. The results showed that in the first cycle the average student learning outcomes were 63% complete, while in the second cycle the average student learning outcomes were 93% complete. These results indicate that the use of the Canva application in the application of the Project Based Learning (PJBL) model can improve the learning outcomes of class X IPAS 8 SMAN 11 Banda Aceh even semester of the 2022/2023 school year